A Comparison Between ISO-Certified And Non ISO-Certified Colleges On Service Quality In Higher Education: Student's Perception. - Zailani, Suhaiza; Jauhar, Junaimah; Othman, Rosly; Ng, Lee Yen (2006)
Higher education is characterized by a higher degree of interpersonal contact,complexity, divergence, and customizations than other service businesses.